A tarefa de casa na inclusão escolar: Alunos com deficiencia física - Gregorutti, Carolina Cangemi [UNESP]; Zafani, Mariana Dutra [UNESP]; Omote, Sadao [UNESP]; Baleotti, Luciana Ramos [UNESP] (FapUNIFESP (SciELO), 2017)
Homework (HW) can contribute to the achievement of meaningful learning and complement and strengthen classroom activities.This study aimed to identify and analyze how HW is being proposed for students with physical disabilities (PD) integrated into regular education classes, from the perception of teachers and family caregivers. Fifteen teachers and the same number of family caregivers of children with PD took part on this study. Two semi-structured interview scripts were used for data collection, each one for a distinct group (teachers and family caregivers). The interviews were recorded and transcribed for further analysis and categorization. The results suggest that the teacher, in many cases, does not adjust the HW to suit the demands of the student, or does not provide the same amount of HW for the student with PD than does for other students. Regarding the families, the results indicate that they perceive the child’s difficulties and at the same time, anguish over with the lack of communication with the school, which leads to concerns and doubts about the performance of the student. The results of this study may be useful in the context of inclusive education, because a well-managed HW can acquire a particularly interesting function as a mediator between school and family.
Homework and school inclusion: Students with physical disabilities
Keywords: Family caregivers; Homework; Physical disabilities; Special education; Teacher